Composition and doping control for metal–organic chemical vapor deposition of InP-based double heterojunction bipolar transistor with hybrid base structure consisting of GaAsSb contact and InGaAsSb graded layers. (19th June 2017) - Hoshi, Takuya; Kashio, Norihide; Sugiyama, Hiroki; Yokoyama, Haruki; Kurishima, Kenji; Ida, Minoru; Matsuzaki, Hideaki
Abstract: We report on a method for composition and doping control for metalorganic chemical vapor deposition of a double heterojunction bipolar transistor (DHBT) with a hybrid base structure consisting of a compositionally graded InGaAsSb for boosting an average electron velocity and a heavily doped thin GaAsSb for lowering the base contact resistivity. The GaAsSb contact layer can be formed by simply turning off the supply of In precursor tetramethylindium (TMIn) after the growth of the composition and doping graded InGaAsSb base. Consequently, the solid composition and hole concentration of hybrid base can be properly controlled by just modulating the supply of only TMIn and carbon tetrabromide. Secondary ion mass spectroscopy for the DHBT wafer reveals that the contents of In, Ga, and C inside the base are actually modulated from the collector side to the emitter side as expected. Transmission-line-model measurements were performed for the compositionally graded-InGaAsSb/GaAsSb hybrid base. The contact resistivity is estimated to be 5.3 Ω µm 2, which is lower than half the value of a compositionally graded InGaAsSb base without the GaAsSb contact layer. The results indicate that the compositionally-graded-InGaAsSb/GaAsSb-contact hybrid base structure grown by this simple method is very advantageous for obtaining DHBTs with a very high maximum oscillation frequency.